Development of a New 24-bit High-Performance Chipless RFID Tag for Accurate Identification in IoT Systems - Kawther Mekki; Omrane Necibi; Noureddine Boulejfen; Samia Larguech; Norah Muhammad Alwadai; Ali Gharsallah (IEEE Access, 2023)
Chipless RFID has the potential to bring in a paradigm change in industrial applications, notably in the world of the Internet of Things (IoT). This wireless technology permits distant identification, sensing, and tracking, giving tremendous development prospects. Despite substantial advances over the previous century, designing high-performance chipless RFID for IoT applications remains a problem. This research presents a new chipless planar RFID tag for item tracking and identification in IoT systems. The suggested tag uses numerous T-shaped slow-wave structures as micro-reflecting resonators with different dimensions on a lossy substrate to encode information in the tag’s backscattered signal after illumination. The mutual coupling between the resonators has been minimized to improve tag performance and printing variety. A tag with a coding capacity of 24 bits and a compact size of $60×40$ mm2 was simulated in CST Microwave Studio to validate the suggested approach. To create tags, several patterned configurations were applied on a Rogers RO4350B substrate, and their radar cross-section responses were studied. When compared to typical multi-resonator tags, the suggested tag design demonstrated excellent downsizing and efficient frequency spectrum usage. Furthermore, the Q-factor and coding strength were both high, showing that the suggested technology is capable of manufacturing high-performance chipless tags.